Impact of Marketing Mix on Patient Perception and Loyalty: Dampak Bauran Pemasaran terhadap Persepsi dan Loyalitas Pasien - supardi; Fahmi, Shiddiqi (Journal of Islamic and Muhammadiyah Studies, 2024)
This study investigates patient perceptions of the marketing mix and its impact on loyalty at Muhammadiyah Probolinggo Mother and Child Hospital. Through quantitative analysis of questionnaire responses, the study explores the relationship between patient perceptions and loyalty, employing observational survey methods. Findings reveal that patient perceptions, particularly of service quality, place, and tariff, significantly influence loyalty. While there's a positive perception of the marketing mix overall, areas like promotion need improvement. The study underscores the importance of understanding patient perceptions to enhance loyalty and suggests strategies for hospital management to improve patient experience and foster loyalty, contributing to healthcare service quality enhancement. Highlight: Perception affects loyalty: Quantitative analysis reveals marketing mix influence. Marketing mix impact: Quality, place, tariff influence patient loyalty. Management implications: Enhance perception, improve service for increased loyalty. Keywoard: Patient Perception, Marketing Mix, Loyalty, Muhammadiyah Probolinggo Hospital, Quantitative Analysis